P264 Community perspectives on bacterial STI testing for gay, bisexual and other men who have sex with men in toronto, canada. (14th July 2019) - Gesink, Dionne; Burchell, Ann; Logie, Carmen; Nelson, Laron; Rana, Jayoti; Wang, Susan; Lisk, Ryan
Abstract : Background: Clinical guidelines recommend that sexually active men who have sex with men (MSM) get tested for bacterial STIs at least once a year, and as often as every 3 months if at ongoing risk. However, few MSM follow this guideline in practice. Our aim was to explore MSM perspectives regarding STI testing services for MSM in Toronto. Results were used to identify and prioritize new STI testing interventions in Toronto. Methods: We conducted 4 focus groups with gay, bisexual and other MSM (gbMSM) in 2017: two with HIV-positive cis-identified gbMSM (n=16), one with HIV-negative cis-identified gbMSM (n=8), and one with trans-identified gbMSM (n=3). Participants were asked about their experience with STI testing in Toronto, barriers and facilitators to testing, and the ideal STI testing process. Focus groups audio recorded, transcribed verbatim, and analyzed using thematic analysis. Results: Major themes centred around deficits in existing clinic contexts and ways to improve them, options for testing services outside of clinics, integration with healthcare, and compassionate care. Participants desired accessible locations/hours; minimal wait times; express/streamlined testing; improved clinic atmosphere/ambience; and minimal crowding/interaction in waiting rooms. Suggested alternatives included online/home testing; routinizing testing with other services; pharmacies; and clinics at sex-based venues, schools, workplaces, and ASOs. Some participants desired more healthcare continuity in the context of STI testing, and spoke of needs for linkages to primary/HIV care with providers who are welcoming to MSM and transmen. Participants consistently underlined the need to minimize STI-related stigma with compassionate, professional, and non-judgemental care. Conclusion: Participants offered concrete and practical solutions for improving existing services. Their views may also guide efforts to implement new strategies such as online testing. Optimal STI testing would offer variety and choice in the range of testing options available, and would be part of person-centred, LGBT-affirming care. Disclosure: No significant relationships.